Microaggressions, diabetes distress, and self-care behaviors in a sample of American Indian adults with type 2 diabetes. - Sittner, Kelley J.; Greenfield, Brenna L.; Walls, Melissa L. (Journal of Behavioral Medicine, 2018)
American Indian/Alaska Native people experience the highest age-adjusted prevalence of type 2 diabetes of any racial group in the United States, as well as high rates of related health problems. Chronic stressors such as perceived discrimination are important contributors to these persistent health disparities. The current study used structural equation modeling to examine the relationships between racial microaggressions, diabetes distress, and self-care behaviors (diet and exercise) in a sample of 192 American Indians with type 2 diabetes from the northern United States. We found that microaggressions was positively associated with diabetes distress and that microaggressions had an indirect link to self-care via diabetes distress. Diabetes distress is an important mechanism linking microaggressions to self-care behaviors, which are critical to successful disease management and the reduction of complications. The amelioration of diabetes distress could improve self-care even in the presence of pervasive, chronic social stressors such as microaggressions.